2017
DOI: 10.1007/s12667-017-0234-z
|View full text |Cite
|
Sign up to set email alerts
|

Optimizing day-ahead bid curves in hydropower production

Abstract: In deregulated electricity markets, hydropower producers must bid their production into the day-ahead market. For price-taking producers, it is optimal to offer energy according to marginal costs, which for hydropower are determined by the opportunity cost of using water that could have been stored for future production. At the time of bidding, uncertainty of future prices and inflows may affect the opportunity costs and thus also the optimal bids. This paper presents a model for hydropower bidding where the b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
4
2
1

Relationship

3
4

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 15 publications
(36 reference statements)
0
17
0
Order By: Relevance
“…Bids for all time periods of the following day are typically submitted simultaneously with no provision for contingent bids on their reservoir levels. This imposes a daunting task on these producers to determine their optimal bidding strategies [1], [2], since it requires them to base their decisions on projections of market supply and demand dynamics to compute the expected prices for each of the bidding time periods of the next day. This becomes particularly difficult in a market with large share of renewable energy sources (RES), increasing stochastic supply-side variations.…”
Section: A Motivation and Backgroundmentioning
confidence: 99%
“…Bids for all time periods of the following day are typically submitted simultaneously with no provision for contingent bids on their reservoir levels. This imposes a daunting task on these producers to determine their optimal bidding strategies [1], [2], since it requires them to base their decisions on projections of market supply and demand dynamics to compute the expected prices for each of the bidding time periods of the next day. This becomes particularly difficult in a market with large share of renewable energy sources (RES), increasing stochastic supply-side variations.…”
Section: A Motivation and Backgroundmentioning
confidence: 99%
“…This method has been extended to a stochastic programming model for optimization of bids in [14]. For the current topic, it is important to emphasize that the method involves solving stochastic MILPs in iterations and that each model instance thus should be solved within a few minutes.…”
Section: The Hydropower Bidding Problemmentioning
confidence: 99%
“…Use of continuous variables means that it is possible to turn a generator on by a fractional amount. This does not correspond to any feasible operating point, but it might be a reasonable approximation when calculating marginal costs, especially since it is currently not possible to use the full MILP formulation due to time constraints [14]. In [15], it is found that using a linear approximation to start-ups gives an average deviation of 0.01% from the objective function value of the equivalent binary formulation.…”
Section: Simulationmentioning
confidence: 99%
See 2 more Smart Citations